2012
DOI: 10.1109/tifs.2012.2217332
|View full text |Cite
|
Sign up to set email alerts
|

Monogenic Binary Coding: An Efficient Local Feature Extraction Approach to Face Recognition

Abstract: Abstract:Local feature based face recognition (FR) methods, such as Gabor features encoded by local binary pattern, could achieve state-of-the-art FR results in large-scale face databases such as FERET and FRGC. However, the time and space complexity of Gabor transformation are too high for many practical FR applications. In this paper, we propose a new and efficient local feature extraction scheme, namely monogenic binary coding (MBC), for face representation and recognition. Monogenic signal representation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 48 publications
0
50
0
Order By: Relevance
“…The ability of 2D Gabor filter to clearly describe the local characteristics of both high-and low-frequencies in the imagery has facilitated its successful application in high-resolution remote sensing imagery segmentation [26,29]. An even-symmetric linear Gabor filter has the following form [30]:…”
Section: Feature Extractionmentioning
confidence: 99%
“…The ability of 2D Gabor filter to clearly describe the local characteristics of both high-and low-frequencies in the imagery has facilitated its successful application in high-resolution remote sensing imagery segmentation [26,29]. An even-symmetric linear Gabor filter has the following form [30]:…”
Section: Feature Extractionmentioning
confidence: 99%
“…Recently, the combination of a Riesz-based method and LBP has been shown to be an effective way for many applications [16,24,33]. Moreover, Lei et al [19] developed an approach to exploit the neighbouring relationship in the spatial domain and various Gabor faces.…”
Section: Riesz-based Volume Local Binary Patterns (Rvlbp)mentioning
confidence: 99%
“…Recent studies [9,16,24,33,35,36] have demonstrated the local image information can be well characterized in a unified theoretic framework, namely the Riesz transform. Felsberg and Sommer proposed to use the Riesz transform for image processing [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve high recognition accuracy the extracted features are fused. The experimental results show that MBC based feature extraction method achieves high accuracy with lower time and space complexity [8].…”
Section: Introductionmentioning
confidence: 98%